The Effect of Health Education on PCOS Using Video Media on the Knowledge of First-Year Female Students in the S1 Nursing Study Program at STIKes RSPAD Gatot Soebroto - Dinda Aryanti; Siti Rochanah; Laela Larasati (JOURNAL EDUCATIONAL OF NURSING(JEN), 2026)
Polycystic Ovary Syndrome (PCOS) is one of the hormonal disorders commonly occurring in women of reproductive age, including female students. Knowledge about PCOS is very important so that female students can recognize signs, symptoms, and early prevention of complications. However, the basic knowledge of first-year students is generally still low, requiring effective education methods. The research design used a pre-experimental approach with a one-group pretest-posttest design and a sample of 65. Results from the Kolmogorov-Smirnov normality test showed a p-value of 0.200 > 0.05, indicating normally distributed residuals. The hypothesis test using the Simple Paired T-test yielded a p-value of 0.001 < 0.05, accepting H1. Conclusion: Health education using video media proved effective in increasing knowledge among female students at STIKes RSPAD Gatot Soebroto.